Metafungsi Videografi Unmanned Aerial Vehicle Pada Konten Komunikasi Publik Pemerintah - Pinem, Citra Danta; Zarkasi, Irwa Rochimah (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Using unmanned aerial vehicle or drone videography in video content creation can explore new things. Images will be more diverse with explorative angles, and drones emerge as a new alternative in public communication with many advantages. Government agencies that present information to the public also use drone technology. One is a report on various Presidential activities carried out by the Presidential Secretariat Office. Various media often make video content on the official account of the Presidential Secretariat as a reference or news source. Of course, there are many meanings that the video maker (account owner) wants to convey to its audience (the public). This research uses social semiotic analysis to find the meaning and purpose behind the making of the activity video on the official account of the Presidential Secretariat. The results obtained are a description of Indonesia's natural beauty, the people's hospitality, the President's image, and the government's commitment to various aspects such as infrastructure, politics, socio-culture, security, economy, and tourism. It also shows the unity of ASEAN countries towards a common goal and the hope of making ASEAN the epicenter of growth, a peaceful, stable, and prosperous region.